(untitled) (Journal of Parents and Teachers, 2013)
This article deals with the importance of literature with one’s inner life. In the inner life are the basic spiritual functions as intelligence, imagination, desire and will. It has to be cultivated internalizing external stimuli in order to awaken our feelings and emotions. Literature is a meeting with oneself, with the others and with their feelings and experiences. Reading is, as the author says, a window to the world. The reader reads in order to meet himself inside what he reads. In the same way, writing is the best way to express our inner life, to find ourselves, to communicate, just for pleasure, etc. Finally, the author concludes that there is not literature without inner life.